Studi Literatur: Peran Audit Berbasis EDP dalam Proses Audit Internal dan Eksternal - Aydina Salsabila; Elyanti Rosmanidar; Indah Juliantika; Nasya Rizki Buana; Rifda Yasirah; Riska Diyanti; Tia Ahmad (ICONS: Islamic Economics Journal, 2025)
This study is a literature review that aims to examine the role of audits using Electronic Data Processing (EDP) in internal and external audits in the digital age. EDP enables faster, more accurate, and more efficient data processing, as well as improving the effectiveness and reliability of audits. In internal audits, EDP helps monitor internal controls and improve operational efficiency, while in external audits, EDP is used for testing and analyzing financial statements.The implementation of EDP also has challenges, such as data security risks and the need for training for auditors. Therefore, the application of technology in auditing is very important to improve the quality of supervision and internal control. The results of the study show that the combination of technology use and auditor skills is very important to obtain good audit results. This study provides an understanding of the benefits and challenges of implementing EDP-based auditing and its impact on current auditing practices.